PHYTOREMEDIATION OF HYDROCARBON-CONTAMINATED SOILS USING JARAK KEPYAR (Ricinus communis L) AND COMPOST - Firman Hidayat Madubun; Radjali Amin; Dewi Rahyuni (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2020)
Phytoremediation is known as one of the bioremediation techniques which may remove, stabilize, and/or destroy contaminants in the media. This study was aiming at collecting evidence of phytoremediation, which was applied with the addition of compost. Jarak Kepyar (Ricinus communis L.) was selected for this study because its seeds highly potency as biodiesel raw materials. Laboratory research scale was prepared, and the experiment design was complete random design with three replications. The experiment design was a full random design with three replications. The treatments were mixed contaminated soil (contaminated soil: compost = 3:1) and R. communis; and mixed garden soil (soil:compost=3:1) and R. communis; and contaminated soil without compost and R. communis. The statistical t-Test with a range of confidence at 95% showed that the phytoremediation significantly removed the Total Petroleum Hydrocarbons (TPH) at 97.7%. TPH accumulations were detected in roots and shoot ranged from 3377.6 mg/kg to 3555.0 mg/kg. R. communis leave development was the most sensitive indicator to biotoxicity of the hydrocarbons in the soils.